Optimizing the ARQ performance in downlink packet data systems with scheduling - Haitao Zheng; Viswanathan, H. (IEEE transactions on wireless communications, 2005)
Third generation wireless systems typically employ adaptive coding and modulation, scheduling, and Hybrid Automatic Repeat reQuest (HARQ) techniques to provide high-speed packet data service on the downlink. Two main considerations in designing such a system are algorithms for the selection of coding and modulation schemes based on the channel quality of the link and algorithms for the selection of the user to whom a particular slot is assigned. We propose a systematic approach to optimize the mapping between signal-to-interference-and-noise ratio (SINR) and modulation and coding scheme (MCS) to maximize the throughput by taking into account the type of HARQ scheme employed. We also propose to incorporate frame error rate (FER) and retransmission information as a part of the scheduling decision. The proposed scheduler ranking methods based on using an effective rate rather than the instantaneous rate provide natural priority to retransmissions over new transmissions, and priority to users with better channel quality. Extensive simulation results comparing performance of the proposed methods to conventional methods are presented.